In-vitro efficacy of two spectrophotometer-based shade matching systems for color matching of ceramics after artificial accelerated aging - Alqahtani, Fawaz (Brazilian Dental Science, 2021)
Objective: The objective of the present invitro study was to verify the efficacy of two spectrophotometer-based shade matching systems for color matching of ceramics after artificial accelerated aging (AAA). Material and Methods: : The ceramics used were porcelain laminated veneers. Seventy standard-shaped discs (thickness x diameter: 0.5 mm x 10 mm) of B1 shades were used. Based upon the type of resin cement used, the specimens were divided into seven groups (10/group). The following light-cured cements were used: RelyX-Veneer (L-RV), Variolink-Veneer (L-VV), and VariolinkEsthetic (L-VE). The dual-cured cements were: RelyX Ultimate (D-RU), RelyX-Unicem (D-RC), and Variolink-Esthetics DC (D-VE). The control group consisted of ceramic only. All specimens were thermocycled in water for 3,500 cycles between 5 o C -55 o C, with dwell times of 30 s in each bath and a transfer time of 10 s between baths. All specimens were thermocycled in water for 3,500 cycles between 5 o C and 55 o C, and color measurement was done using the VITA Easyshade and ColorEye spectrophotometers. Baseline color reading was performed 24-hours after cementation. Differences in color (DE) of EasyShade and ColorEye before and after AAA were determined and compared statistically. Group comparisons were done using the paired t-tests. Level of significance was set at P< 0.05. Results: The mean differences in color (DE) values obtained from EasyShade spectrophotometer for light- and dual-cured cements, were  0.843±0.89 (Lc1), 4.11±0.69 (Lc2) and 0.833±0.47 (Lc3); and 2.22±0.64 (Dc1), 3.37±0.83 (Dc2) and 0.38±0.92 (Dc3), respectively. The mean differences in color (DE) values obtained from ColorEye spectrophotometer for light- and dual-cured cements, were 0.68±0.86 (Lc1), 4.55±0.83 (Lc2) and 2.68±0.26 (Lc3); and 2.06±0.84 (Dc1), 1.8±1.08 (Dc2) and 0.96±0.71 (Dc3), respectively. There was no significant difference in the mean DE values among the groups. Conclusion: The VITA Easyshade and ColorEye shade matching systems are comparable in terms of their efficacy for color matching of cerammics after AAA. KeywordsArtificial accelerated aging; Color matching; In vitro; Porcelain veneer; Spectrophotometer.